Promoting Student's Problem-Solving Skills through STEM Project-Based Learning in Earth Layer and Disasters Topic - Firdha Sarah Kartini; Ari Widodo; Nanang Winarno; Lia Astuti (Journal of Science Learning, 2021)
Located in the Pacific Ring of Fire, Indonesia is endangered by natural disasters. Through the changing of learning activity in a proper way by the application of STEM Project-Based Learning, future generations are expected to develop the knowledge and thinking skill to solve the problem. Therefore, this study aimed to investigate implementing STEM Project-Based Learning on student's Problem-Solving Skills. This research used a Pre-Experiment method with a One-Group Pretest-Posttest design and essay questions as data collection tools. In this research, 30 7th-grade students at one school in Bandung, Indonesia, were chosen as the participants. The data analysis showed significant improvement between student's Problem-Solving skills pretest and post-test (N-Gain=0.73). In addition, Idea-Finding is the most significant improvement during the Fact-Finding on the lowest. Based on the result, STEM Project-Based Learning is recommended to improve students' Problem-Solving Skills since they can use their integrated knowledge to solve a real-world problem.